Neurophysiological Correlates of Gait in the Human Basal Ganglia and the PPN Region in Parkinson’s Disease - Molina, Rene; Hass, Chris J.; Sowalsky, Kristen; Schmitt, Abigail C.; Opri, Enrico; Roper, Jaime A.; Martinez-Ramirez, Daniel; Hess, Christopher W.; Foote, Kelly D.; Okun, Michael S.; Gunduz, Aysegul (Frontiers in Human Neuroscience, 2020)
This study aimed to characterize the neurophysiological correlates of gait in the human pedunculopontine nucleus (PPN) region and the globus pallidus internus (GPi) in a Parkinson’s disease (PD) cohort. Though much is known about the PPN region through animal studies, there is limited physiological recordings from ambulatory humans. The PPN has recently garnered interest as a potential deep brain stimulation (DBS) target for improving gait and freezing of gait (FoG) in PD. We used bidirectional neurostimulators to record from the human PPN region and GPi in a small cohort of severely affected PD subjects with FoG despite optimized dopaminergic medications. Five subjects, with confirmed on-dopaminergic medication FoG, were implanted with bilateral GPi and bilateral PPN region DBS electrodes. Electrophysiological recordings were obtained during various gait tasks for five months post-operatively in both the off- and on-medication conditions (obtained during the no stimulation condition). The results revealed suppression of low beta power in the GPi and a 1-8 Hz modulation in the PPN region which correlated with human gait. The PPN feature correlated with walking speed. GPi beta desynchronization and PPN low frequency synchronization was observed as subjects progressed from rest to ambulatory tasks. Our findings add to our understanding of the neurophysiology underpinning gait and will likely contribute to the development of novel therapies for abnormal gait in PD.